2022
DOI: 10.1111/boer.12367
|View full text |Cite
|
Sign up to set email alerts
|

The expansion of early childcare and transitions to first and second birth in Germany

Abstract: We use quasi‐experimental expansion of publicly funded childcare slots for children under the age of three from Germany and exploit regional variations of this large‐scale expansion to account for endogenous and selective fertility decisions. To account for left and right censoring, we implement this quasi‐experimental framework into the setting of the semiparametric Cox hazard model. By using spatial data on childcare provision at the level of counties and microdata from the German Socio‐Economic Panel (SOEP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Another study examining the same reform using a Cox hazard model (including DiD) found that effects were robust after accounting for internal migration. An increase in childcare coverage increased the probability of first birth among employed native childless couples (Schuss & Azaouagh 2023). No such effect was found regarding the transition to second births.…”
Section: Public Childcarementioning
confidence: 83%
“…Another study examining the same reform using a Cox hazard model (including DiD) found that effects were robust after accounting for internal migration. An increase in childcare coverage increased the probability of first birth among employed native childless couples (Schuss & Azaouagh 2023). No such effect was found regarding the transition to second births.…”
Section: Public Childcarementioning
confidence: 83%
“…This consideration draws attention to the undeniable shortcomings in the overall structure of the Italian system of ECEC provision, which saw in the past two decades only a slow modification toward higher coverage rates. Rather than minor incremental adjustments in childcare coverage at lower levels, implementing substantial reforms in childcare policies and the broader family policies might prove more impactful, not least because reforms can generate awareness regarding the actual level of childcare coverage in one's region, as the German case (Schuss & Azaouagh, 2022) or the Swedish case (Mörk et al, 2013) show. Most likely, only a comprehensive reform of social policies understood as a social investment (Billingsley et al, 2022)-a significant driver of change-has the potential to influence individual perceptions, foster confidence in the future and promote fertility.…”
Section: Discussionmentioning
confidence: 99%